Access to and safety of COVID-19 convalescent plasma in the United States Expanded Access Program: A national registry study - Jonathon W. Senefeld; Patrick W. Johnson; Katie L. Kunze; Evan M. Bloch; Noud van Helmond; Michael A. Golafshar; Stephen A. Klassen; Allan M. Klompas; Matthew A. Sexton; Juan C. Diaz Soto; Brenda J. Grossman; Aaron A.R. Tobian; et al. (2021)
The United States (US) Expanded Access Program (EAP) to coronavirus disease 2019 (COVID-19) convalescent plasma was initiated in response to the rapid spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of COVID-19. While randomized clinical trials were in various stages of development and enrollment, there was an urgent need for widespread access to potential therapeutic agents. The objective of this study is to report on the demographic, geographical, and chronological characteristics of patients in the EAP, and key safety metrics following transfusion of COVID-19 convalescent plasma.